Social preferences, monopsony and government intervention - Laszlo Goerke; Michael Neugart (Canadian Journal of Economics/Revue canadienne d'économique, 2021)
Monopsony power by firms and social preferences by consumers are well established. We analyze how wages and employment change in a monopsony if workers compare their income with that of a reference group. We show that the undistorted, competitive outcome may no longer constitute the benchmark for welfare comparisons and derive a condition that guarantees that the monopsony distortion is exactly balanced by the impact of social comparisons. We also demonstrate how wage restrictions and subsidies or taxes can be used to ensure this condition, both for a welfarist and a paternalistic welfare objective.
Keywords: 330